Questioning the concept of culture in mainstream occupational therapy/Questionando o conceito de cultura nas linhas de terapia ocupacional domintantes - Dos Santos, Vagner; Leon Spesny, Sara (Cadernos Brasileiros de Terapia Ocupacional, 2016)
It has been about 25 years since the concepts of culture and diversity were included in the theoretical sight of occupational therapy. Once a matter of anthropological discussion, occupational therapy recognized the value of thinking about culture and the diverse forms of human presence in the world. In this sense, occupational therapy has dawned from anthropology its cultural ‘curiosity’. Thus, in this essay we aim to contextualize what we call mainstream occupational therapy and its use of culture. We did not focus over any theoretical or practical models, but rather on shared views of this concept at the international level. This is followed by a reflection upon this concept from an anthropological perspective, that avoids culturalist explanations. Finally we argue for an epistemological use of culture within occupational therapy. Throughout this essay we also drive a critical reflection of the influence of the Global North values within occupational therapy’s implementation and development in the Global South.